Adición de cannabis de la variedad Cherry Oregon en el agua como promotor de crecimiento en gallinas Lohman Brown en la etapa de postura. - Vera Almache, Karelis Rosemary (2025)
In the present experimental research work was carried out with the purpose of testing Cannabis in small doses in water in Lohman Brown hens in the laying stage, at the Faculty of Agricultural Sciences of the Veterinary Medicine career of the Babahoyo canton of the Los Ríos Province. We worked with 68 hens, distributed completely randomly, experimentally designed the blocks with three repetitions by four treatments. The amount of treatments that were used varies from 0 g, 10 g, 15 g, 20 g, three groups that worked with, (T0) 10g was added, (T1) with 0g, (T2) with 15g, (T3) with 20g of cannabis per 10 liters of water. The research was conducted with the following results: T0, which was supplemented with 0 g of cannabis in the water, yielded 5.26 L of waste in both water and feed, and a total egg weight yield of 2711,1 g. T1, with 10 g of cannabis, yielded 7,49 L of water waste and a total egg weight yield of 2822,94 g; T2 yielded a total egg weight of 2740,914 g and a water waste of 6,76 L., T3 showed a higher egg weight yield of 3261,78 g and a waste of 9,19 L. The resulting data provide reliable information for the development and performance of hens, as cannabis promotes growth, laying, and animal welfare. It was concluded that Cherry Oregan cannabis, in addition to being an alternative food, helps reduce the risk of disease, is beneficial for egg production, and is also a growth promoter.